2019
DOI: 10.1097/cji.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor-modified Donor Lymphocyte Infusion Improves the Survival of Acute Lymphoblastic Leukemia Patients With Relapsed Diseases After Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: The value of chimeric antigen receptor-modified donor lymphocyte infusion (CAR-DLI) is unclear in B-cell acute lymphoblastic leukemia (B-ALL), particularly in patients with relapsed diseases after allogeneic hematopoietic stem cell transplantation (allo-HSCT). In this study, 5 B-ALL patients who relapsed after allo-HSCT received CAR-DLI (CAR-DLI group), and the outcome was compared with 27 relapsed B-ALL patients who received DLI therapy (DLI group). The median complete remission duration of CAR-DLI group was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…used CAR T cells as DLI treatment, which significantly prolonged the survival period. They found a lower incidence of aGVHD than that of traditional DLI ( 31 ).…”
Section: Discussionmentioning
confidence: 91%
“…used CAR T cells as DLI treatment, which significantly prolonged the survival period. They found a lower incidence of aGVHD than that of traditional DLI ( 31 ).…”
Section: Discussionmentioning
confidence: 91%
“…The two quasi-experimental studies assessing OS 31 , 32 showed longer OS with CAR-T versus DLI therapy in R/R B-ALL patients (Wang et al. 31 DLI median 3.7 months (range 0–65); CAR-T median 12 months (range 3–29); p = 0.049.…”
Section: Resultsmentioning
confidence: 99%
“…One RCT was reclassified as NRSI and another one was classified as an ongoing RCT and was not still included because of its preliminary status only providing immature data for its primary outcome. 28 Therefore, two RCTs 29 , 30 and nine NRSI (two quasi-experimental studies 31 , 32 and seven cohort studies) 33 39 assessing the use of CAR-T in 1221 participants with B-cell lymphoma or T or B-cell acute lymphoblastic leukemia were included in the review. A detailed list with reasons for exclusion is presented in Supplemental Appendix 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The details have been described previously. 19,20 Disease assessments were performed prior to and after ASCT therapy (1, 3, 6, 9, 12 months) with positron-emission tomography and computed tomography (PET/CT) or CT. Patient response was evaluated utilising the 2007 revised response criteria for malignant lymphoma.…”
Section: Study Design and Participantsmentioning
confidence: 99%